Penggunaan Media Dakon Satuan Panjang Berbantuan Model Make a Match terhadap Hasil Belajar Matematika Siswa Kelas IV di SDN 15 Mataram - Ni Luh Arginda Pasmawangi; A. Hari Witono; Baiq Mariana (Mataram University, 2026)
This study aimed to improve the mathematics learning outcomes of fourth-grade students at SDN 15 Mataram through the use of a dakon length-unit learning medium combined with the Make a Match learning model. The research employed Classroom Action Research (CAR) conducted in two cycles involving 34 students. Data were collected through learning outcome tests administered in the Pretest phase, Cycle I, and Cycle II, and were analyzed descriptively and quantitatively based on the class average, classical completeness, and N-Gain scores. The findings showed a consistent improvement in students’ achievement from the initial condition to Cycle II. In the Pretest stage, the class average was 65.6 with a classical completeness rate of 35.29%. After the implementation of the action in Cycle I, the average increased to 73.0 with a classical completeness rate of 67.65%, although this had not yet met the success indicator. After reflective improvement in Cycle II, the average score rose significantly to 83.0 and classical completeness reached 91.18%, exceeding the minimum mastery criterion (MMC) of 75. The N-Gain score also increased from 0.21 in Cycle I to 0.51 in Cycle II, indicating a moderate and meaningful improvement in learning outcomes. These results suggest that the use of the dakon length-unit medium integrated with the Make a Match learning model can create a more active, enjoyable, and contextual learning environment, thereby helping students better understand length unit conversion concepts. Therefore, this approach proved effective in significantly improving the mathematics learning outcomes of fourth-grade students.